The Evolution of the Accounting Practices During the Recent Economic Crisis: Empirical Survey Regarding the Earnings Management - Cătălina Gorgan; Vasile Gorgan; Valentin Florentin Dumitru; Ileana Cosmina Pitulice (Amfiteatru Economic Journal, 2012)
Financial markets rely on confidence and confidence is supported by the presumption that financial statements are accurate and reflect the economic reality. Financial scandals from 2001-2002 as well as the recent economic crisis have raised questions about the integrity of accounting information provided to investors and other categories of users. In this context, our study aims to analyze the extent to which financial reporting is involved in financial crisis and, on the other hand to outline the changes produced by the crisis in the quality of financial information reported by companies. The main objective of the paper consist in arguing that earnings management by discretionary accruals for big European companies decline during the recent economic crisis compared to previous period.
Keywords: M41; 330; discretionary accruals; earnings management; accounting information quality; international financial reporting standards (IFRS); economic crisis